(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
To accurately simulate photovoltaic (PV) modules, it is essential to have access tocharacteristics that are not included in the manufacturer’s data sheet. Emerging photovoltaic technologyincludes perovskite solar cells made from organometal halides. The precursor to today’s widely usedperovskite solar cells was the dye-sensitized cell. Light from visible sources may be converted intodirect current using photovoltaic cells (PV cells), which are specialized semiconductor diodes (DC).Certain PV cells may even convert UV or IR light into DC current. We used a Non-Linear Equation Derivedfrom an Electrical Circuit to determine the features of photovoltaic modules for static and dynamicstudies of medium voltage electrical energy systems, Newton’s and Two-step procedures, andmathematical approaches. When compared to NRM, the suggested technique yields the highestefficiency, and all the necessary computations are performed in a MATLAB environment. In the end, thisstudy provides a quick and easy mathematical technique that may be used in real-world solar electricalengineering challenges.